Analisis Kebutuhan Pengembangan Media Diorama Augmented Reality Untuk Pembelajaran IPAS di Sekolah Dasar - Kadek Panji Yustisio; I Gede Suwindia; Ni Putu Candra Prastya Dewi (Cetta: Jurnal Ilmu Pendidikan, 2026)
IPAS learning in elementary schools still faces limitations in providing learning media that effectively facilitate students’ concrete and contextual understanding of ecosystem concepts, which affects their engagement in learning about the relationships and dynamics of biotic and abiotic components. This study aims to analyze the needs for developing Augmented Reality (AR) Diorama media in IPAS learning as a basis for designing media that aligns with user characteristics and instructional contexts. A descriptive approach was employed by integrating quantitative and qualitative data obtained from Grade V teachers and students through needs analysis questionnaires and classroom observations. The results indicate that IPAS learning is predominantly supported by textbooks and two-dimensional media, which are insufficient to explain abstract and dynamic ecosystem concepts; teachers require interactive visual media to support explanations of ecological relationships and processes, while students demonstrate strong interest in three-dimensional visual learning media. The availability of supporting devices in the school environment provides opportunities for implementing AR-based media, although media design should consider existing technical constraints. In conclusion, AR Diorama media is relevant to be developed as an innovative, contextual, and applicable alternative to enhance the quality of IPAS learning in elementary schools.